2004
DOI: 10.1002/ijc.20342
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP‐ribosyl)ation inhibitors: Promising drug candidates for a wide variety of pathophysiologic conditions

Abstract: Poly(ADP-ribose) polymerases are involved in many aspects of regulation of cellular functions. Using NAD ؉ as a substrate, they catalyse the covalent transfer of ADP-ribose units onto several acceptor proteins to form a branched ADP-ribose polymer. The best characterised and first discovered member of this multiprotein family is PARP-1. Its catalytic activity is markedly stimulated upon binding to DNA strand interruptions, and the resulting polymer is thought to function in chromatin relaxation as well as in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 54 publications
1
52
0
1
Order By: Relevance
“…PARP-1 inhibition has been the focus of extensive research as a radiosensitizer/ chemosensitizer based on evidence implicating a role for PARP-1 (and PARP-2) in DNA damage repair and survival of cells under genotoxic stress (3,9). The potential application and preclinical development of PARP inhibitors as radiosensitizers/chemosensitizers, until recently, was limited by their potency, selectivity, and pharmaceutical properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PARP-1 inhibition has been the focus of extensive research as a radiosensitizer/ chemosensitizer based on evidence implicating a role for PARP-1 (and PARP-2) in DNA damage repair and survival of cells under genotoxic stress (3,9). The potential application and preclinical development of PARP inhibitors as radiosensitizers/chemosensitizers, until recently, was limited by their potency, selectivity, and pharmaceutical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Poly(ADP-ribose) (PAR) polymerase (PARP)-1 belongs to the PARP enzyme family that currently includes 18 members; of these members, only PARP-1 and PARP-2 play a role in DNA damage and repair (3,4). PARP-1 is activated by, and implicated in, base excision repair of DNA strand breaks caused by ionizing radiation, or following enzymatic repair of DNA lesions induced by methylating agents, topoisomerase I inhibitors, and other chemotherapeutic agents, such as cisplatin and bleomycin (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Potential applications in the nonmalignant setting have recently been reviewed (56,57). In the realm of cancer therapy, preclinical models have shown that inhibition of PARP-1 can potentiate the activity of both radiotherapy and a variety of chemotherapeutic agents (58 -64), and PARP-1 inhibitors have also shown single-agent activity against certain tumor cell lines (65,66).…”
Section: Parp Inhibitorsmentioning
confidence: 99%
“…Alterations of PAR metabolism are causally involved in the pathogenesis of inflammatory [18] and autoimmune disease [19] , ischemia reperfusion injury in brain [20] , heart and intestine [21][22][23] , neuronal degeneration and neurotoxicity [24] , genetic and genomic instability (reviewed in [25]) and cancer (reviewed in [26,27] ). Targeting of the poly(ADP-ribose) metabolic pathway has therefore become an important focus in research on cancer therapy (recent reviews in [28][29][30]), cardiovascular disease intervention [31][32][33][34] and a number of other pathophysiological conditions [35,36] . Because of the potential of PAR metabolism as a drug target, identification of the key players appears to be crucial.…”
Section: Introductionmentioning
confidence: 99%